DETERMINAN KINERJA PELAYANAN KESEHATAN IBU DAN ANAK DI RUMAH SAKIT PEMERINTAH INDONESIA (ANALISIS DATA RIFASKES 2011) - Ernawati, Demsa Simbolon Djazuli Chalidyanto (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: The hospital has quite an important role inreducing IMR and MMR because hospitals as providers ofplenary personal health services including maternal and childhealth (MCH). However, until now the IMR and MMR Indonesiais still high compared to other ASEAN countries. The maincauses of maternal mortality are obstetric complications ordisease as a complication that arises during pregnancy, childbirthand postpartum. This factor was experienced by approximately20% of all pregnant women, while complication cases thatwere treated well are less than 10%.Objective: The research aims to identify the effect of hospitalcharacteristics, management of MCH services, humanresources for MCH, MCH services, and MCH equipment on theperformance of MCH services in government hospitals inIndonesia.Methods:Research is using secondary data of Health FacilitiesResearch 2011 (RIFASKES) with a cross sectional study.Population and sample is the entire Indonesian governmenthospitals (685 hospitals). The research variables wereidentified from the available variables in the questionnaireRIFASKES. Performance measurement of the compositevariable proportion of maternal deaths due to hemorhage dâ1%, dâ 10% pre-eclampsia, sepsis dâ 0.2%, dâ 20% secariasection, the proportion of stillborn dâ 4%, and the proportion ofLBW handling 100% based SPM hospital. Multivariate logisticregression was used to obtain a model determinants ofperformance MCH services.Results: The majority (66.3%) government hospitals inIndonesian has less than optimal performance. As thedeterminant is unaccredited status (OR = 2.99: 1.43 to 6.28),the hospital is not a vehicle of education (OR = 1.78; 1.11 to2.85), team PONEK is incomplete (OR = 1.89; 1.27 to 2.82),there is no PONEK-trained doctor in the ER (OR = 1.89; 1.27 to2.82), there is no team ready to perform the operation or taskthough on call (OR = 2.16; 1.32 to 3.53). The most dominantfactor is the unaccredited status.Conclusions: Suboptimal performances of MCH at Indonesiangovernment hospitals are influenced by the low hospital servicecharacteristics and incomplete of human resources. TheMinistry of Health needs to support improvement in all types ofservices to complete an accredited hospitals (16 types ofservices), not just 5 or 12 services. They also need to makethe government hospital as a vehicle of education, increasethe quantity and quality of human resources are trained inPONEK-skill, ensure availability of PONEK-trained doctor inemergency, provide the team that are ready to perform theoperation or task though on call, and increase organizationalcommitment to overall performance improvement.Keywords: Performance, Maternal and Child Health Services,Government Hospital